2022
DOI: 10.1186/s12883-022-02550-3
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilesional volume loss of basal ganglia and thalamus is associated with poor hand function after ischemic perinatal stroke

Abstract: Background Perinatal stroke (PS) is the leading cause of hemiparetic cerebral palsy (CP). Involvement of the corticospinal tract on neonatal magnetic resonance imaging (MRI) is predictive of motor outcome in patients with hemiparetic CP. However, early MRI is not available in patients with delayed presentation of PS and prediction of hemiparesis severity remains a challenge. Aims To evaluate the volumes of the basal ganglia, amygdala, thalamus, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 49 publications
3
15
0
Order By: Relevance
“…In contrast, the diagnostic criteria for PVI ( Kirton et al, 2008 ) deliberately include sparing of the caudal basal ganglia (specifically the putamen) which is not typically drained by the medullary venous system ( Raets et al, 2015 ). Likewise, a recent study has shown that ipsilesional volume loss in the basal ganglia due to perinatal stroke was associated with poor hand function, however this relationship was highly dependent on the type of stroke ( Ilves et al, 2022 ). Given the extensive functions of the basal ganglia, damage to these structures may result in complex disabilities following perinatal stroke but their role remains poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the diagnostic criteria for PVI ( Kirton et al, 2008 ) deliberately include sparing of the caudal basal ganglia (specifically the putamen) which is not typically drained by the medullary venous system ( Raets et al, 2015 ). Likewise, a recent study has shown that ipsilesional volume loss in the basal ganglia due to perinatal stroke was associated with poor hand function, however this relationship was highly dependent on the type of stroke ( Ilves et al, 2022 ). Given the extensive functions of the basal ganglia, damage to these structures may result in complex disabilities following perinatal stroke but their role remains poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…(30) Previous studies have consistently reported that neonates with reduced basal ganglia volumes experience more developmental delays and deficits than their healthy counterparts. (31)(32)(33)(34)(35) Smaller subcortical structures are associated with poor motor and higher-order executive functions, as found in the 7-year follow-up of neonates born with HIE. (36) We also found that HIE severity was associated with subcortical volumes, particularly impacting the basal ganglia, adjusting for clinical and demographic factors, including TH.…”
Section: Hie Newborns Healthy Newbornsmentioning
confidence: 82%
“…Thus, even a small reduction in the volume of these regions may result in functional changes. 26 On cognitive testing, PWH were slower to complete a motor task measuring manual dexterity with their dominant hand. It is possible that this impairment may be related to reductions in basal ganglia volume, a region important in motor pathways.…”
Section: Discussionmentioning
confidence: 99%